Removal of ferum ion from wastewater by using thin film composite membrane / Norin Zamiah Kassim Shaari, Nurul 'Izzati Mohamad and Nurul Aida Sulaiman - Kassim Shaari, Norin Zamiah; Mohamad, Nurul 'Izzati; Sulaiman, Nurul Aida (Universiti Teknologi MARA Shah Alam, 2018)
In this study, the thin film composite membrane (TFC) was fabricated to remove ferum ion from wastewater. The composite membrane was fabricated using polysulfone as the support membrane with two formulations of barrier layer; membrane from polymer blend of polyvinyl alcohol (PVA)/Chitosan and membrane from hybrid formulation of the polymer blend with tetraethyl orthosilicate (TEOS). Prior to the membrane filtration process, the wastewater was characterised in term of pH, turbidity, chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solid (TSS), and concentration of ferum ion. By comparing with Standard B effluent quality for discharge, the wastewater qualities were not conformed to the standard in term of COD, pH and ferum concentration. After pH adjustment was conducted on the wastewater, it was filtered through the two types of the thin film composite, respectively. The effect of pH and formulation of the barrier layers on the percentage removal of ferum ion was investigated. Based on the result, higher removal of ferum ion (99.89%) could be achieved by using TFC with hybrid membrane especially at pH 10 as compared to TFC with polymer blend.